Application of Multiobjective Optimization Based on Modified SPEA2 Method for Tuning FOPID plus Second-Order Derivative Controller in Hydraulic Turbine Governing System - Tian Tian; Qiang Huang; Jinhua Lv; Mo Zhou; Jian Tang (Journal of Electrical and Computer Engineering)
The controller design and parameter tuning of the hydraulic turbine governing system are critical for ensuring stability and safety of operation. In this study, we propose a novel design of fractional-order PID plus second-order derivative (FOPID2D) controller design for the HTGS system. In addition, we develop a modified strength Pareto evolutionary algorithm II (MSPEA2) to optimize the design parameters with multiple objectives. By combining fractional calculus and second-order derivative, the FOPID2D controller offers enhanced control flexibility compared to conventional PID controller. To achieve the Pareto-front, we employ the proposed MSPEA2 method as an optimizer, which is further improved using a Uniform–Cauchy–Gaussian hybrid mutation strategy. We demonstrate its numerical quality and diversity superiority over the conventional method through test function results. The designed FOPID2D controller, along with PID, fractional-order PID, and PID plus second-order derivative controllers, is employed in the load disturbance experiments of the hydraulic turbine governing system. Consequently, the control effect of the proposed FOPID2D controller is validated by comparison with other controllers.